Origin and Pathways of Dissolved Organic Carbon in a Small Catchment in the Lena River Delta - Stolpmann, Lydia; Mollenhauer, Gesine; Morgenstern, Anne; Hammes, Jens S.; Boike, Julia; Overduin, Pier Paul; Grosse, Guido (Frontiers in Earth Science, 2022)
The Arctic is warming due to climate change. The accelerated warming causes permafrost thaw and therefore the mobilization of organic carbon from especially old ice-rich yedoma deposits. Dissolved to aquatic systems, DOC can be transported and degraded further downstream. Here, we analyse the influence of lakes and ponds, which are interposed in a stream catchment, on DOC concentrations and export. We identify the origin of DOC in a small catchment and how it may transform on its flow pathway to the river outlet. In addition to DOC concentrations we use radiocarbon dating of DOC as well as stable isotopes of hydrogen and oxygen from lakes and ponds, inflow and stream samples , and discharge measurements from a small lake catchment on Kurungnakh Island in the central Lena River Delta. We find an abrupt decrease in DOC concentration where yedoma thaw streams of high DOC concentration reach the thermokarst lake Lucky Lake with oldest DOC ages in our study site, which is attributed to mobilized old yedoma and Holocene carbon. The overall dilution with the big lake water volume of Lucky Lake with lower DOC concentrations and lake processes such as mineralization are major causes of DOC changes in the lake. After Lucky Lake drains into Lucky Lake stream, we find progressively younger DOC ages to the mouth at the Olenyokskaya Channel paired with decreasing DOC concentrations. A result of dilution with leaching water and rapid emission of ancient yedoma carbon to the atmosphere. Our study shows that thermokarst lakes and ponds may act as DOC filters by diluting incoming waters of higher DOC concentrations and modifying DOC to carbon dioxide and methane.